EVALUASI KEBIJAKAN SANITASI AIR DALAM UPAYA PENYEDIAAN AIR BERSIH BAGI MASYARAKAT: Studi : Pada Desa Weekurra, Kecamatan Wewewa Barat, Kabupaten Sumba Barat Daya, Provinsi Nusa Tenggara Timur - ali hanafiah; Moses Agustinus D.L (JOURNAL AKSES STIA MALANG, 2023)
Water sanitation development is an important aspect in achieving public health and welfare in Indonesia. However,the problem of water sanitation is increasingly complex and difficult to solve. This study aims to evaluate watersanitation policies in an effort to provide clean water for the community, as well as analyze the factors that supportand hinder the implementation of water sanitation policies. The research method used is descriptive, focusing onWeekurra Village, West Wewewa District, Southwest Sumba Regency, East Nusa Tenggara Province. TheGovernment of Southwest Sumba realizes that Weekurra Village has potential natural resources that can be used tomeet water sanitation needs and increase access to adequate clean water. Although water sanitation services areavailable in Weekurra Village, residents still have to travel a long distance (about 1.3 km) with about 16 minutes,through inadequate roads, to get clean water. This is a worrying problem. An inhibiting factor in the provision of cleanwater is the uneven distribution, where some regions have not benefited. This is due to the long distance betweenwater sources and residents' residences, as well as the lack of budget to build pipeline infrastructure and waterreservoirs for each individual. Based on research findings, there are several problems that have not been solved Therefore, several suggestions were proposed, among others: cooperation between the Village Government and theRegency Government of South West Sumba to formulate regulations governing sanitation and the provision of cleanwater, to ensure the need for clean water can be fulfilled properly as a basic human need. In addition, it is expectedthat there will be sufficient budget to build facilities and infrastructure such as storage tanks and pipe systems as aneffort to distribute clean water to the community in Weekurra Village